Targeting Nicotinic Receptors for Parkinson's Disease Therapy - Quik, Maryka; Bordia, Tanuja; Huang, Luping; Perez, Xiomara (CNS & Neurological Disorders - Drug Targets, 2011)
A promising target for improved therapeutics in Parkinson's disease is the nicotinic acetylcholine receptor (nAChR). nAChRs are widely distributed throughout the brain, including the nigrostriatal system, and exert important modulatory effects on numerous behaviors. Accumulating evidence suggests that drugs such as nicotine that act at these sites may be of benefit for Parkinson's disease treatment. Recent work indicates that a potential novel therapeutic application is the use of nicotine to reduce levodopa-induced dyskinesias, a side effect of dopamine replacement therapy for Parkinson's disease. Several clinical trials also report that nicotine may diminish disease symptoms. Not only may nAChR drugs provide symptomatic improvement, but they may also attenuate the neurodegenerative process itself. This latter idea is supported by epidemiological studies which consistently demonstrate a ∼50% reduced incidence of Parkinson's disease in smokers. Experimental work in parkinsonian animal models suggests that nicotine in tobacco may contribute to this protection. These combined findings suggest that nicotine and nAChR drugs offer the possibility of improved therapeutics for Parkinson's disease.
Keywords: Alzheimers disease